Teologia e literatura: uma reflexão sobre a Teologia da Redenção pela humanização a partir da antropologia presente no romance d’A Pedra do Reino, de Ariano Suassuna - Silva, Dayvid da (2024)
The following research aims to reflect on the Redemption (theology) based on a work of literature, namely, the Romance d’A Pedra do Reino, by Ariano Suassuna. Highlighting this novel, we can realize that its author, Ariano Suassuna, through the character “Quaderna” and also “Rapaz-do-cavalo-branco”, seeks to show that, through celebration, laughter, dreaming, it is possible to defeat suffering and living a reality redeemed from pain, helping to struggle the hardships of life. Thus, Quaderna seeks a redemption on his own history and the Rapaz-docavalo-branco is seen as a messiah kind, who comes to redeem the poor and suffering people, inaugurating a kingdom of peace and joy, in which laughter is the mark of redemption. In this way, we can infer that redemption – generally present in events such as incarnation, paschal event and even the end of times – is a reality that can be experienced in everyday life through a process of humanization, that is, the human condition can be redeemed through redemptive acts that occur in everyday life. According to this, we ask ourselves: isn't that Christ's salvation project? Isn't redemption the overcoming of suffering, as the gospels witness to? All of this made us understand that, in theology, redemption needs to be understood as much more than a justification of the sinful condition and a divinization that disregards humanization as an elemental result of Jesus' action. In this sense, we consider that redemption through humanization is what makes us understand the salvation of Jesus Christ. From his birth to the Easter event and even with his glorious coming, the mission of Jesus Christ is to redeem human beings, making them fully human and full of dignity